A critical review of public health interventions aimed at reducing alcohol consumption and/or increasing knowledge among pregnant women. (20th May 2014) - Crawford‐Williams, Fiona; Fielder, Andrea; Mikocka‐Walus, Antonina; Esterman, Adrian
Abstract Issues It is well established that alcohol can cross the placenta to the fetus and can affect both physical and psychological development of the infant; however, many women continue to drink during pregnancy. It is therefore important to determine whether interventions can be successful in reducing alcohol consumption among pregnant women. Past reviews have investigated the effectiveness of clinical interventions in reducing alcohol consumption in pregnancy; however, the aim of the current review was to focus on the effectiveness of public health interventions. Approach A critical literature review was conducted by searching several electronic databases using key words such as 'pregnancy', 'alcohol', 'interventions' and 'public health'. Studies were included if they utilised a public health intervention and included alcohol consumption or levels of knowledge as an outcome measure. Key Findings Seven studies were included in the review. Interventions included multimedia and educational interventions. Improvements in knowledge were reported in six studies, whereas one study found contradictory results. Four studies used alcohol consumption rates as an outcome measure, and although a reduction in consumption was reported, the results were non‐significant. Implications The effectiveness of public health interventions that aim to increase awareness and reduce alcohol consumption among pregnant women cannot be assessed because of the paucity of studies. Conclusions The results of this critical review emphasise a lack of evidence and highlight the need for further evaluation research on this topic. [Crawford‐Williams F, Fielder A, Mikocka‐Walus A, Esterman A. A critical review of public health interventions aimed at reducing alcohol consumption and/or increasing knowledge among pregnant women. Drug Alcohol Rev 2015;34:154–61]